Having learned a lot about the arithmetic and geometric sequences, most people are used to expressing the nth term of a sequence un in the form un=u1+d(n-1) for the arithmetic sequence and un=u1*rn-1 for the geometric sequence. However, there are some sequences for which it is hard to tell whether they are geometric or arithmetic (as the one described above), and yet, there are methods of finding the expression for their nth term without the need to do it.
We know that Sn=u1+u2+...+un. But also Sn-1=u1+u2+...+un-1. Hence, to find the expression for un it is sufficient to compute the value of Sn-Sn-1! Sn-Sn-1= 3n2 - 2n - 3(n-1)2 + 2(n-1) = 3n2 - 2n - 3(n2 - 2n + 1) + 2n - 2 = 3n2 - 2n - 3n2 + 6n - 3 + 2n - 2 = 6n - 5. Hence un = 6n - 5.